In vitro antiprotozoal activity and cytotoxicity of extracts and isolated constituents from Greenwayodendron suaveolens. (4th December 2016) - Muganza, D. Musuyu; Fruth, B.; Nzunzu, J. Lami; Tuenter, E.; Foubert, K.; Cos, P.; Maes, L.; Kanyanga, R. Cimanga; Exarchou, V.; Apers, S.; Pieters, L.
Abstract: Ethnopharmacological relevance: The Nkundo people (Nkundo area of Bolongo, Mai-Ndombe district, Bandundu Province, DR Congo) use various plant parts of the tree Greenwayodendron suaveolens (Engl. & Diels) Verdc. (syn. Polyalthia suaveolens Engl. & Diels) (Annonaceae) against malaria, but its antiprotozoal constituents are not known. Materials and methods: The crude 80% ethanol extract from the fruits, leaves, root bark and stem bark and 16 fractions were assessed in vitro for their antiprotozoal activity against Trypanosoma brucei brucei, T. cruzi, Leishmania infantum and the chloroquine and pyrimethamine-resistant K1 strain of Plasmodium falciparum ( Pf -K1). Their cytotoxic effects were evaluated against MRC-5 cells. Active constituents were isolated by chromatographic means, identified using spectroscopic methods, and evaluated in the same assays. Results: The root bark extract showed the highest activity against P. falciparum K1 (IC50 0.26 µg/mL) along with the stem bark alkaloid fraction (IC50 0.27 µg/mL). The root bark alkaloid fraction had a pronounced activity against all selected protozoa with IC50 values <1 µg/mL. The 90% methanol fractions of the different plant parts showed a pronounced activity against P. falciparum K1, with IC50 values ranging between 0.36 µg/mL and 0.69 µg/mL. Four constituents were isolated: the triterpenes polycarpol, and dihydropolycarpol, the latter one being reported for the first time from nature, and the alkaloids polyalthenol and N-acetyl-polyveoline. They were active to a various degree against one or more protozoa, mostly accompanied by cytotoxicity. The highest selectivity was observed for N -acetyl-polyveoline against P. falciparum K1 (IC50 2.8 µM, selectivity index 10.9). Conclusions: These results may explain at least in part the traditional use of this plant species against parasitic diseases such as malaria in DR Congo. Graphical abstract: